National Archive Modernization Project: Records Management and Technology for Digital Transformation (GESTIÓN Y TENDENCIAS, 2020)
That technology has revolutionized our lives is nothing new; we see the advances and their influence on our lives and our surroundings every day and never cease to be amazed. There is, however, one aspect that has not received the visibility and prominence it deserves, since it has a cross-cutting and direct effect on our lives, on our daily routine, on how we relate to the State and how the State relates to citizens. We refer to the change the public administration is undergoing in the way it carries out the procedures that affect citizens and in its internal management. Adapting technology to these areas has a direct bearing on records management and archives.